MODERN PUBLIC ADMINISTRATION METHODS IN THE ECONOMIC REFORMS OF UZBEKISTAN (World Economics and Finance Bulletin, 2026)
This article examines the implementation of modern public administration methods in Uzbekistan’s economic reforms. Institutional changes led by the Administration of the President of the Republic of Uzbekistan and the Cabinet of Ministers of the Republic of Uzbekistan, including digital transformation and performance-based management, are analyzed as key drivers of economic efficiency. The findings show that modern governance approaches enhance economic stability and investment attractiveness